Exploiting Cancer Cell Vulnerabilities to Develop a Combination Therapy for Ras-Driven Tumors - De Raedt, Thomas; Walton, Zandra; Yecies, Jessica L.; Li, Danan; Chen, Yimei; Malone, Clare F.; Maertens, Ophélia; Jeong, Seung Min; Bronson, Roderick T.; Lebleu, Valerie; Kalluri, Raghu; Normant, Emmanuel; et al. (Cancer cell, 2011)
Ras-driven tumors are often refractory to conventional therapies. Here we identify a promising targeted therapeutic strategy for two Ras-driven cancers: Nf1-deficient malignancies and Kras/p53 mutant lung cancer. We show that agents that enhance proteotoxic stress, including the HSP90 inhibitor IPI-504, induce tumor regression in aggressive mouse models, but only when combined with rapamycin. These agents synergize by promoting irresolvable ER stress, resulting in catastrophic ER and mitochondrial damage. This process is fueled by oxidative stress, which is caused by IPI-504-dependent production of reactive oxygen species, and the rapamycin-dependent suppression of glutathione, an important endogenous antioxidant. Notably, the mechanism by which these agents cooperate reveals a therapeutic paradigm that can be expanded to develop additional combinations. ► We describe a promising combination therapy for two aggressive Ras-driven cancers ► mTOR and HSP90 inhibitors cooperate to exert potent activity in mouse models of MPNST and NSCLC ► These agents function by promoting irresolvable ER and oxidative stress ► Combinatorial therapy can capitalize on cellular vulnerabilities of cancer cells